Removal Efficiency of Nitrite and Sulfide Pollutants by Electrochemical Process by Using Ti/RuIrO2 Anode - Aris Mukimin; Agus Purwanto (Indonesian Journal of Chemistry, 2018)
In general, wastewater treatment by physical, chemical and biological methods are only focused on TSS, BOD and COD removals that the effluent still contains anion pollutant as NO2- and S2-. Electrochemical technology is a proper method for those pollutants treatment due to its fast process, easy operation and minimum amount of sludge. Electrocatalytic reactor with 8 L capacity using Ti/RuIrO2 cylinder as anode and Fe plate as cathode was arranged and applied to treat anion pollutants. Hydraulic retention time (30, 60, 90 and 120 min), salt concentration (250, 500 and 750 mg/L) and voltage (4, 5, and 6 V) were chosen as operation variables and NO2- and S2- concentrations as parameter indicators. Nitrite removal efficiency reached 75 and 99.7% after 60 and 120 min of electrolysis, respectively, while sulfide could obtain higher efficiency, i.e., 97 and 99.9% after 60 and 90 min, respectively, at operation variables of potential of 5 V and salt of 500 mg/L. Removal process is dominated by indirect oxidation mechanism by HClO/ClO- oxidators generated at anode surface as intermediate products. The lifespan of electrode and electric consumption are two main factors of operation cost. Electric consumed was 0.452 kWh per 1 g nitrite removed.